2022
DOI: 10.1039/d2ob00908k
|View full text |Cite
|
Sign up to set email alerts
|

Azirine-triazole hybrids: selective synthesis of 5-(2H-azirin-2-yl)-, 5-(1H-pyrrol-2-yl)-1H-1,2,3-triazoles and 2-(5-(2H-azirin-2-yl)-1H-1,2,3-triazol-1-yl)pyridines

Abstract: Azirine-triazole hybrids, 1-R-5-(3-aryl-2H-azirin-2-yl)-1H-1,2,3-triazoles, were selectively synthesized by reaction of 1-(3-aryl-2H-azirin-2-yl)-2-(triphenylphosphoranylidene)ethanones with tosyl and (E)-2-benzoylvinyl azides in high yields at rt. The reaction with 2-azidopyridine makes it possible to obtain azirine-triazole-pyridine...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Scheme 5. Relative Gibbs free energies for the transformations of pyrenyl-and dinyl-substituted nitrile ylides (in kcal/mol, 298 K, DFT B3LYP-D3/6-311+G(d,p) level with model for MeCN) [43]. Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 5. Relative Gibbs free energies for the transformations of pyrenyl-and dinyl-substituted nitrile ylides (in kcal/mol, 298 K, DFT B3LYP-D3/6-311+G(d,p) level with model for MeCN) [43]. Scheme 5.…”
Section: Resultsmentioning
confidence: 99%
“…Azirine 32, linked to acridine by a triazole bridge, was also synthesized by the reaction of 1-(3-phenyl-2H-azirin-2-yl)-2-(triphenylphosphoranylidene)ethanone 30 with 9-azidoacridine 31, according to the procedure developed in the work [43], at a 77% yield (Scheme 7). However, the photolysis of azirine 32 in acetonitrile, in the presence of DMAD or PMI (20 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Compared by the reaction with TsN 3 , the reaction with TfN 3 yields α‐diazo ketones instead of azirine‐triazole hybrids (Scheme 23). [39] The decomposition of the starting materials or products have blocked the reaction with BnN 3 in refluxing toluene. DFT calculations suggested that the reactions of α‐carbonylphosphoranes with both sulfonyl azides and alkyl azides proceed via a non‐concerted mechanism, involving the attack of the terminal azide nitrogen on the phosphorane nucleophilic C1 to form the intermediate zwitterion and its cyclization and elimination of triphenylphosphine oxide to 1,5‐disubstituted triazoles.…”
Section: Reaction Of 2h‐azirinesmentioning
confidence: 99%